Media Sosial Instagram Sebagai Sarana Promosi Untuk Meningkatkan Minat Beli Konsumen (Studi Kasus Pada Mini Organic Mart Surabaya) - Yulianti, Risma; Yuliati, Nuriah; Andrian Syah, Mirza (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
Mini Organic Mart is a retail business that offers quality healthy and organic products. Mini Organic Mart has been promoting using social media, especially Instagram, since 2016, but the way to attract consumer attention through social media is still limited. Based on a preliminary survey, the average number of